HUBUNGAN TINGKAT STRES DENGAN SIKLUS MENSTRUASI PADA SISWI KELAS XII SMA N 5 KOTA BENGKULU - Novriani, Febby (Politeknik Kesehatan Kemenkes Bengkulu, 2015)
Adolescence period is an important period in the life span of adolescents when theyare experiencing a transitional period of individual in finding into adulthood. The early years ofmenstruation are the period that susceptible to disturbance, 75% of women in adolescent havesustain disorder with menstruation that is irregular menstruation. The purpose of this study was todetermine the correlation between stress and we menstrual cycle in female students of XII classesat SMA N 5 Bengkulu City 2014. The study design that used was Descriptive Analytic design byusing cross sectional, population in this study were all female students of class XII consist of 106people, technique sampling used total sampling. Data Analysis were univariate and bivariate. Theresults showed that almost all respondents (84.2%) have irregular menstrual patterns. The resultsof the chi square expressed the relationship and stress levels and the menstrual cycle (p = 0.000)It is recommended to the school as a place of education for girls, school is expected to assist thestudent information about how to prevent the occurrence of stress, arrenge schedule with considencein getting relax and rest time for girls student do not that student does not feel burdenedwith activities and school schedules both in academic and non-academic, to reduce the risk ofstress on the students.